Distributional effects of monetary policy in Norway - Yasin Mimir; Mathis Mæhlum; Kjersti Næss Torstensen (Norges Bank, 2021)
We quantify the short-term effects of both non-systematic and systematic monetary policy on the income and wealth distribution in Norway, and measure the relative importance of the various channels. An expansionary monetary policy shock is found to disproportionally benefit the young as well as households with middle to lower income and wealth, and it reduces inequality in disposable income and wealth. The key channel for disposable income is the savings redistribution channel, whereby households with high debt-to-income ratios gain relatively more from a lower interest rate. Because of the high home ownership rate in Norway, most households gain from higher house prices, but the middle and lower part of the distribution gain relatively more as they are more indebted. We also find that systematic monetary policy, aimed at stabilizing cyclical fluctuations in output and inflation, also tends to stabilize income and wealth inequality.
hdl:11250/2735200
Keywords: E2; E3; E5; G5; 330; Monetary policy; Inequality; Household heterogeneity; Income and wealth distribution